Acicular, but not globular, titanium dioxide nanoparticles stimulate keratinocytes to produce pro‐inflammatory cytokines. Issue 5 (12th March 2013) - Hiroike, Mizuho; Sakabe, Jun‐ichi; Kobayashi, Miwa; Shimauchi, Takatoshi; Ito, Taisuke; Hirakawa, Satoshi; Inoh, Akinori; Tokura, Yoshiki
Abstract Titanium dioxide (TiO2) nanoparticles, widely used for daily products, are believed to be biologically inert, but they may cause adverse effects on cells, presumably depending on the particle size and shape. One of the critical targets of TiO2 particles is epidermal keratinocytes, and their initial response to TiO2 may be production of pro‐inflammatory cytokines. We therefore investigated the effects of four types of TiO2 particles on cytokine expression/production by real‐time reverse transcription polymerase chain reaction and enzyme‐linked immunoassay. The TiO2 particles included three acicular types, FTL‐100 (length, 1.68 μm; diameter, 130 nm), FTL‐200 (2.86, 210) and FTL‐300 (5.15, 270), and one globular type, PT‐301 (diameter, 270 nm). Normal human epidermal keratinocytes (NHEK) were cultured with each of the TiO2 particles. During cultivation, the acicular forms of TiO2 were seen by scanning electron microscopy to be internalized by NHEK. The three acicular particles increased the mRNA expressions and supernatant productions of interleukin (IL)‐1α, IL‐1β, IL‐6, tumor necrosis factor‐α and IL‐8 in particle number‐dependent manners, whereas globular PT‐301 had very weak activity. Thus, TiO2 particles may induce skin inflammation depending on the size and shape, providing knowledge on their health usage.